Hypercanonical Joyce: Sam Selvon's The Lonely Londoners, creative disaffiliation, and the global afterlives of Ulysses. Issue 2 (1st February 2022) - Ward, Kiron
ABSTRACT: Roughly two-thirds of the way through Sam Selvon's The Lonely Londoners (1956), there is a section highly redolent of the 'Penelope' episode of James Joyce's Ulysses (1922). Commonly referred to as 'Summer', the section's similarity to 'Penelope' has not gone unnoticed among either Joyce or Selvon scholars; to date, however, only J. Dillon Brown (2013) has offered a substantive reading of the connection. This article seizes on the relative absence of critical discussion of Selvon in Joyce studies to consider what might be the particular responsibilities that Joyce studies bears when reading Joyce's global afterlives. Drawing on critical debates around the concept of global modernism, I discuss the terms of Joyce's canonisation and his use in 'diffusionist' models of literary history. Building on Kandice Chuh's (2019) analysis of the combined effects of liberal representational politics and hypercanonicity in literary studies, I contend that future studies of Joyce's global reception and influence should seek to establish mutually transformative intercultural dialogue, which in turn requires opening the field to unsettling Joyce's position in literary studies – and, to that I end, I propose that Selvon's novel provides an exemplary model of engagement with Joyce through 'creative disaffiliation'.